Persistent dropping an efficient control of traffic aggregates. - Jamjoom, Hani (Computer communication review.)
Flash crowd events (FCEs) present a real threat to the stability of routers and end-servers. Such events are characterized by a large and sustained spike in client arrival rates, usually to the point of service failure. Traditional rate-based drop policies, such as Random Early Drop (RED), become ineffective in such situations since clients tend to be persistent, in the sense that they make multiple retransmission attempts before aborting their connection. As it is built into TCP's congestion control, this persistence is very widespread, making it a major stumbling block to providing responsive aggregate traffic controls. This paper focuses on analyzing and building a coherent model of the effects of client persistence on the controllability of aggregate traffic. Based on this model, we propose a new drop strategy called persistent dropping to regulate the arrival of SYN packets and achieves three important goals: (1) it allows routers and end-servers to quickly converge to their control targets without sacrificing fairness, (2) it minimizes the portion of client delay that is attributed to the applied controls, and (3) it is both easily implementable and computationally tractable. Using a real implementation of this controller in the Linux kernel, we demonstrate its efficacy, up to 60% delay reduction for drop probabilities less than 0.5.